Hybrid Broadcast Encryption and Group Key Agreement Protocol with Precise Cipher Texts - et. al., Chinnala Balakrishna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In cryptographic system so as to manage the group of members, the group key management protocol is used and it also should provide the security to the group of members which means the communication among the members will be done in secure manner. Broadcast Encryption (BCE) provides a key it arise common for all the members in the group during the encryption and all the associated members can decipher the message with the same mutual key but cannot stop decrypt the message by individuals. Broadcast encipher algorithm sends a secure transmit note to the entire members with the distributed key to decrypt the message with trusted third party. The conventional BE scheme fully relies on third party reliable key generator server machine, the responsibility of the third party server is to generating the undisclosed deciphering keys for the entire collection members and the group members are responsible for decrypt the messages which are encrypted under a common encrypted key. The purpose of Group Key Accord (GKAP) protocol is for negotiate all the assembly members and designing a familiar encryption key through the network. With the GKAP the group members are responsible for generating universal encipher key and it permits simply the group people to decrypt the cipher text which is encrypted by group members by using the shared encryption key but this GKA protocol it is not possible to exclude any members from the group to decrypt the cipher text shared under the common encryption key. In this paper we will combine these two techniques to produce a novel approach called as the Hybrid Broadcast Encryption (HBCE). In this innovative primeval all the cluster of participants agree and produces a widespread encipher key but though each individual having their own decipher key, So that the sender by looking the encryption key he will bound the deciphering to limited members for his abundance.